Runoff Analysis in The Telomoyo River Basin - Ratna Septi Hendrasari; Ilham Satriya Aji Wicaksana (Jurnal Studi dan Aplikasi Teknik Sipil (JSATS), 2025)
Surface runoff occurs due to rain falling and flowing over the ground surface. This is due to the intensity of the rain exceeding the infiltration capacity. This surface runoff will combine and flow into the river. This causes an increase in the amount of flow in the river. A large increase in flow that exceeds the capacity of the river can cause water overflows. This can cause flooding. The Telomoyo River Watershed is a watershed located in Kebumen Regency, Central Java Province. In this watershed, the Telomoyo River flows. When there is heavy rainfall, the amount of runoff flowing into the Telomoyo River is large. This condition can cause a large increase in river flow. Surface runoff calculations are carried out by determining the Nakayasu synthetic unit hydrograph and calculating effective rainfall. Based on the analysis results, the maximum runoff that occurs can be approximated by the equation 141.16 Ln (x) + 917.22. Meanwhile, runoff depth increases with increasing effective rainfall. The runoff depth can be approximated by the equation y = 0.1253x – 0.0679.